Biological transformed cannabinoids bee pollen: A symbiosis approach on Apis mellifera raising protocol in Cannabis sativa L. (Hemp) cultivar in Samoeng District, Chiang Mai, Thailand - Chooprasit, Charn; Wongsiri, Siriwat; Varith, Jaturapatr; Daengprok, Wichittra; Ariyadet, Chalinda; Aroonsrimorakot, Sayam (Interdisciplinary Research Review, 2020)
Honey bees (Apis mellifera) and Hemp plants (Cannabis sativa L.) have been recognized as sacred insects and sacred plants and also played as boosters in the world economy. Hemp pollens collected by honey bees for their nutrients and cannabinoids discrete from cannabis plants have not been synergized in business management. A symbiosis approach was adopted in this novel experimental method. This research aimed to investigate the presences of Cannabinoids (CBD, THC and CBN) via a prototype of bee-raising protocol foraging in hemp cultivar to collect hemp pollens. Theoretically, in-hived stored hemp pollen shall embrace active compounds as being abundance in hemp plants, thru biological extraction process. In the field experiment, seed production hemp cultivated in Samoeng, Chiang Mai was fully covered by mosquito net to confine honey bees during male flowering. The extraction of those cannabinoids of in-hived stored pollen samples and their abundances were conducted by GC-MS technique. A repeated measure ANOVA model was conducted for statistical analysis. The experimental research results indicated the first ever found of cannabinoids presented in in-hived stored pollen samples of all treatments adopted bee raising protocol. The statistical analysis among all treatments contained different means of detected Cannabinoids (CBD, THC and CBN) abundances, which were statistically significant (P-value < 0.0009, <0.0009 and =0.034, respectively). The results were remarkable as shown due to presence of CBD, THC and CBN, as bioactive compounds, in in-hived honey bee pollens that would enlighten an opportunity in managing bee as hemp cultivar either for further academic or business purposes.